Analysis of the Patient Safety Culture in Awal Bros Batam Hospital, Year 2016 - ., Imelda; Wibowo, A (KnE Life Sciences, 2018)
A good patient safety culture is needed as the complexity of hospital services and procedures increase, thus prone to accidental errors. This study aims to find out the cultural status of patient safety in Awal Bros Batam Hospital in the year 2016. The authors used the concept of the patient safety culture of the Agency for Healthcare Research and Quality (AHRQ, 2004) and Carthey and Clarke (2010), and for the improvement of the weak dimensions, the system reliability concept of Marx D. (2010) was used. The study design was sequential explanatory, with Indonesian translation from the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire from AHRQ followed by FGD to formulate the improvement effort of the weak dimension. Patient safety culture status categorized into moderate culture, average of positive perceptions were 70.82%. The greatest strengths were in organizational learning and continuous improvement, feedback and communication about patient safety, and communication openness. Weaknesses were primarily in staffing, nonpunitive responses to errors, handover and transitions must be fixed immediately. Improvement suggestions by reducing non-core job assignments, employee retention programs, hotline service internal, leader lead tracer, and investigator training. Keywords: hospital of patient safety culture, patient safety, safety culture